Effect of Blended Learning On Cost Accounting Academic Evaluation of Student in State University of Malang - Hanjar Ikrima Nanda; Ria Zulkha Ermayda; Dewi Noor Fatikhah R. (Journal of International Conference Proceedings (JICP), 2019)
Products to support blended learning called "Solutive Blended Learning" have been developed. This study aims to evaluate the effectiveness of blended learning using these products, on the learning outcomes of cost accounting for students at State University of Malang. Closed questionnaires were distributed to 32 students who were studying the calculation of manufacturing business production costs, using these products. The independent variables tested were website effectiveness in blended learning management, blended learning concepts, and use of blended learning. The dependent variable is academic evaluation. SPSS 22 is used to make statistical analysis, which uses Pearson correlation test. The results of the analysis show that there is a positive and significant relationship between the use of blended learning, using the products developed, and the results of academic evaluations.